2011
DOI: 10.1007/s00421-011-1843-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acute exercise on endothelial progenitor cells is attenuated in chronic heart failure

Abstract: Exercise training improves endothelial function in patients with chronic heart failure (CHF) through functional enhancement of circulating angiogenic cells and increased numbers of circulating endothelial progenitor cells (EPC). In contrast to healthy subjects, an immediate effect of acute exercise on CD34(+)/KDR(+) EPC is absent in CHF. Whether this reflects an attenuated or rather delayed mobilization, is addressed in the present study by measuring CD34(+)/KDR(+) EPC over a longer time period post-exercise. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 19 publications
(18 reference statements)
2
52
0
2
Order By: Relevance
“…The same research group just recently sought to investigate whether the above result reflected an attenuated or delayed mobilization of EPCs, so they measured CD34 + / KDR + EPCs over a longer time period post-graded exercise testing (GXT). Even though the number of subjects was small (7 CHF patients and 8 healthy controls), the authors reported that EPC numbers increased within 10 min following GXT and remained elevated for up to 2 h. In CHF patients, the initial increase was small and normalized within 30 min [132] . From the current literature it emerges that the acute effect of a single exercise session, either performed as an exercise test, or as a single bout of strenuous exercise, can lead to a significant rise in EPCs in healthy subjects.…”
Section: Effect Of Acute Exercise On Epcsmentioning
confidence: 98%
See 1 more Smart Citation
“…The same research group just recently sought to investigate whether the above result reflected an attenuated or delayed mobilization of EPCs, so they measured CD34 + / KDR + EPCs over a longer time period post-graded exercise testing (GXT). Even though the number of subjects was small (7 CHF patients and 8 healthy controls), the authors reported that EPC numbers increased within 10 min following GXT and remained elevated for up to 2 h. In CHF patients, the initial increase was small and normalized within 30 min [132] . From the current literature it emerges that the acute effect of a single exercise session, either performed as an exercise test, or as a single bout of strenuous exercise, can lead to a significant rise in EPCs in healthy subjects.…”
Section: Effect Of Acute Exercise On Epcsmentioning
confidence: 98%
“…In healthy subjects, tissue ischemia is not normally expected to occur due to exercise, but strenuous exercise at levels above what is defined as anaerobic levels, might induce oxidative stress and an inflammatory response and thus could stimulate the release of EPCs from the bone marrow [121,122] . Researchers have hypothesized [34,132] that, in an attempt to address vascular damage, EPCs show a compensatory increase in patients with mild to moderate CHF. Interestingly, VEGF and SDF are potent angiogenic factors that have been shown to increase after exercise sessions with concomitant rise in EPCs in cardiovascular disease, indicating a possible pathophysiological link.…”
Section: Effect Of Acute Exercise On Epcsmentioning
confidence: 99%
“…We postulate that these EPCs were incorporated in the endothelium, based on previous findings in young healthy men in which an increase in EPCs was noted up to 24 hours after maximal bicycle ergometry. 26 Later, due to long-term healing of endothelium by exercise, the amount of EPCs may decrease again.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the effect of graded exercise testing (GXT) on circulating CD34+/KDR+ EPC and SDF-1␣ serum levels conducted in CHF patients and healthy subjects, patients exhibited a reduced response of circulating EPCs to a maximal exercise bout immediately post exercise compared with healthy subjects; moreover, there was no significant correlation between SDF-1␣ levels and EPCs (Van Craenenbroeck et al, 2011). Notably, the time-course of circulating EPCs following a single exercise bout in patients differed from the biphasic response observed in healthy subjects.…”
Section: Effect Of Exercise On Endothelial Repair Mechanisms In Chfmentioning
confidence: 97%